Biological features of the formation of meat productivity of rabbits of chinchilla breed depending on crossing with meat breeds : ст. - Luchyn, I. S.; Perih, D. P.; Lunyk, Yu. M. (Cherkasy Research Station of Bioresources of the National Academy of Sciences ; Stepan Gzhytskyi National University of Veterinary Medicine and Biotechnologies, 2023)
Rabbit breeding is a special branch of animal husbandry characterized by high fertility and growth intensity. The main way of intensification of rabbit farming involves such selection measures that adapt rabbit populations of keeping in industrial conditions, ensure high reproductive properties of female rabbits, preservation of rabbits in nests, high growth rate, fattening and meat qualities of animals. The research was conducted on the basis of the experimental rabbit farm of the Cherkasy Research Station of Bioresources of the National Academy of Sciences on the population of female chinchilla (Chinchilla) rabbits and males of the Gray giant rabbit (Gray giant rabbit), New Zealand white rabbit (New Zealand white rabbit) and young rabbits obtained from these three combinations. As the result of the conducted research, it was found that under the conditions of intensive production of rabbit meat, the reproductive qualities of female chinchilla rabbits in combination with males of the Gray giant and New Zealand white rabbits breeds increase, namely: high fertility – on 1.8–5.2 %; milk yield – on 1.8–7.4 %. The weight of the nest at weaning was probably (P < 0.001) higher in female rabbits of the combination Chinchilla x New Zealand white rabbit and was 5.29 ± 0.13 kg, which is 869 g more than the purebred peers of the chinchilla breed and 380 g more than the combination Chinchilla x Great giant rabbit. The best indicators of fattening and meat productivity were found in young rabbits of 1/2Chinchilla 1/2Gray giant rabbit and 1/2Chinchilla 1/2New Zealand white rabbit origin. The fattening indicators of the rabbits of these groups compared to the rabbits of the control group accordingly increased: live weight at 90 days of age – on 4.0 and 3.8 % (Р < 0.05); average daily increases – on 4.7 and 5.4 % (Р < 0.05; Р < 0.01); waist width – on 5.6 and 8.7 % (Р < 0.01). The research also revealed that the group of young rabbits 1/2Chinchilla 1/2New Zealand white rabbit by origin had a higher slaughter yield and the indicators of which exceeded and rabbits of the second group ( 1/2Chinchilla 1/2Gray giant rabbit on 3.6% and the first (Chinchilla) – on 4.1 %, and the expenses of feed per 1 kg of increase by group was 3.85 accordingly; 3.75; 3.7 kg. Crossbred rabbits 1/2Chinchilla 1/2New Zealand white rabbit and 1/2Chinchilla 1/2Gray giant rabbit according to this indicator prevailed over purebred peers (Chinchilla) on 2.6 and 3.9 %, accordingly.
Keywords: rabbit breeding; chinchilla; кролівництво; шиншили